Surgical results of endonasal dacrocystorhinostomy - Save, Sneha L.; Jadhav, Priyanka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The lacrimal system includes the tear film of the eye and the tear drainage system. Endoscopic dacryocystorhinostomy (DCR) is a safe and effective method of surgical treatment of nasolacrimal duct obstruction. The anatomy of the nasal cavity is better visualized endoscopically and sac is approached under vision and hence the results are decided at the time of surgery. Methods: Present clinical study was conducted in tertiary medical centre from July 2015 to July 2016. Total 50 patients with epiphora as evidenced by nasolacrimal duct blockage on sac syringing were included in the study. Children less than 10 years and revision cases were excluded. These patients underwent DCR without stenting. Results: Out of the 50 patients, 60% were males and 40% were females. Surgical success was deﬁned as anatomical patency and symptomatic relief at the end of the follow up period which was observed in 45 of 50 (90%) patients. Incidence of complications was as low as only 5 patients. These patients were followed up for 6 months with no complaints of epiphora. Conclusions: Endoscopic DCR is a safe and effective method of surgical treatment of nasolacrimal duct obstruction. It gives equivalent symptomatic relief from epiphora when compared to external method. Thus, we can minimize complications, discomfort, cost of stenting and follow up visits after endonasal surgery. Due to higher success rate, minimal invasiveness and high patient satisfaction as compared to other procedures, it has gained more popularity.